LncMyoD Promotes Skeletal Myogenesis and Regulates Skeletal Muscle Fiber-Type Composition by Sponging miR-370-3p - Zhang, Peiwen (Genes (Basel), 2021)
The development of skeletal muscle is a highly ordered and complex biological process. Increasing evidence has shown that noncoding RNAs, especially long-noncoding RNAs (lncRNAs) and microRNAs, play a vital role in the development of myogenic processes. In this study, we observed that lncMyoD regulates myogenesis and changes myofiber-type composition. miR-370-3p, which is directly targeted by lncMyoD, promoted myoblast proliferation and inhibited myoblast differentiation in the C2C12 cell line, which serves as a valuable model for studying muscle development. In addition, the inhibition of miR-370-3p promoted fast-twitch fiber transition. Further analysis indicated that acyl-Coenzyme A dehydrogenase, short/branched chain (ACADSB) is a target gene of miR-370-3p, which is also involved in myoblast differentiation and fiber-type transition. Furthermore, our data suggested that miR-370-3p was sponged by lncMyoD. In contrast with miR-370-3p, lncMyoD promoted fast-twitch fiber transition. Taken together, our results suggest that miR-370-3p regulates myoblast differentiation and muscle fiber transition and is sponged by lncMyoD.